Hubungan Antara Perempuan Dan Peperangan Dalam Pengalaman Serta Dampaknya Dalam Komunitas Sosial - Soraya Anugrah Rhamadhani; Asep Suherman (CV. ITTC INDONESIA, 2024)
This study explores the connection between women and war, focusing on its impact on social communities, particularly the trauma experienced by women who are victims of conflict. Armed conflicts often place women in the most vulnerable positions, exposing them to gender-based violence such as sexual assault and exploitation. The research draws on trauma theory from Bessel van der Kolk, human rights theory from Jack Donnelly, and Rebecca J. Cook’s theory of special protection for women to examine legal protections, referring to international laws like the CEDAW Convention and humanitarian law, as well as trauma recovery. A legal and normative approach is used to analyze the effectiveness of laws in protecting women affected by conflict. The study aims to provide better policy recommendations for protecting women in conflict zones and improving psychological recovery services and social reintegration. The research finds that the trauma experienced by women victims of conflict is significant and varied, ranging from psychological issues like PTSD (Post-Traumatic Stress Disorder) to social problems like stigma and isolation from their communities. Women often struggle to access psychological support and healthcare, especially in conflict-affected areas. International laws, such as the CEDAW Convention and humanitarian law, have not been fully implemented at the national level to adequately protect women from gender-based violence during conflicts.